Dual-Laboratory Validation of a Method for the Determination of Fructans in Infant Formula and Adult Nutritionals: First Action 2016.14. (22nd November 2019) - Brunt, Kommer; Sanders, Peter; Spichtig, Véronique; Ernste-Nota, Veronica; Sawicka, Paulina; Iwanoff, Kimberley; Van Soest, Jeroen; Lin, Paul Kong Thoo; Austin, Sean
Abstract: Until recently, only two AOAC Official Methods SM have been available for the analysis of fructans: Method 997.08 and Method 999.03. Both are based on the analysis of the fructan component monosaccharides (glucose and fructose) after hydrolysis. The two methods have some limitations due to the strategies used for removing background interferences (such as from sucrose, α-glucooligosaccharides, and free sugars). The method described in this paper has been developed to overcome those limitations. The method is largely based on Method 999.03 and uses combined enzymatic and SPE steps to remove the interfering components without impacting the final analytical result. The method has been validated in two laboratories on infant formula and adult nutritionals. Recoveries were in the range of 86–119%, with most being in the range of 91–104%. RSDr values were in the range of 0.7–2.6%, with one exception when the fructan concentration was close to the LOQ, resulting in an RSDr of 8.9%. The performance is generallywithin the requirements outlined in the AOAC StandardMethod Performance Requirements (SMPR ® 2014.002), which specifies recoveries in the range of 90–110% and RSDr values below 6%.